Non-alcoholic Fatty Liver Disease Causing Platypnea-Orthodeoxia Syndrome - Ali, Hassam (Cureus, 2020)
Non-alcoholic fatty liver disease (NAFLD) with cryptogenic liver cirrhosis is uncommonly linked to platypnea-orthodeoxia syndrome (POS). Traditionally, this syndrome has been described in correlation to intracardiac shunting like patent foramen ovale.  We report a case of a 70-year-old female, with a previous history of NAFLD and heart failure presenting with acute hypoxic respiratory failure secondary to fluid overload. Further investigations revealed cryptogenic presentation of POS, which was masked by her heart failure. The patient was not able to maintain her oxygen saturation levels in an upright position, with marked improvement when lying down. Her echocardiogram was significant for positive bubble study without any intracardiac shunt, hence making NAFLD as a cause of this rare presentation of POS a more likely diagnosis.